Direct Imaging of Charge Redistribution due to Bonding at Atomic Resolution via Electron Ptychography - Jones, Lewys (My University, 2019)
Phase imaging in electron microscopy is sensitive to the local potential including charge redistribution from bonding. We demonstrate that electron ptychography provides the necessary sensitivity to detect this subtle effect by directly imaging the charge redistribution in single layer boron nitride. Residual aberrations can be measured and corrected post-collection, and simultaneous atomic number contrast imaging provides unambiguous sub-lattice identification. Density functional theory calculations confirm the detection of charge redistribution
PUBLISHED